Enantioselective total synthesis of (+)-incargranine A enabled by bifunctional iminophosphorane and iridium catalysis - Miller, AAM; Biallas, P; Shennan, BDA; Dixon, DJ (Wiley, 2023)
Herein we report the first enantioselective total synthesis of (+)-incargranine A, in nine steps. The total synthesis was enabled by an enantioselective intramolecular organocatalysed desymmetrising Michael addition of a malonamate ester to a linked dienone substrate that established pivotal stereocentres with excellent enantio- and complete diastereoselectivity. Furthermore, a key hemiaminal intermediate was accessed by developing an iridium-catalysed reductive cyclisation, and the scope of this transformation was explored to produce a range of bicyclic hemiaminal motifs. Once installed, the hemiaminal motif was used to initiate a biomimetic cascade to access the natural product directly in a single step.